Unlocking the impact of South Africa's correctional centre conditions on inmates' rights - Lalla, Meera (My University, 2017)
Inmates’ rights are of utmost importance in shaping a democratic society based on human dignity, equality and freedom. The State cannot unjustifiably infringe on inmates’ rights and continue to play an active role in exacerbating correctional centre conditions. This study is of significance in confronting the reality of the plight of inmates’ rights violations in a country that is plagued with crime and scepticism towards acknowledging inmates’ rights. The dissertation offers a critical analysis of the impact of South Africa’s correctional centre conditions on inmates’ human rights in a constitutional democracy. The study unlocks three key correctional centre conditions that impact on inmates’ rights. These three correctional centre conditions have been identified as overcrowding, gangsterism and sexual violence, and access to healthcare facilities. In delving deeper into each of the aforementioned correctional centre conditions, international, regional and statutory instruments were examined. Thus, the dissertation also considered the extent of South Africa’s compliance with its international human rights and constitutional obligations to protect and enforce inmates’ rights. The study has investigated the State’s accountability in relation to South Africa’s infringement on inmates’ rights. This endeavour was realised by tracing trends and statistics from State reports. An enquiry into ground-breaking case law addressing the impact of correctional centre conditions on inmates’ rights demonstrated the need for, inter alia, Constitutional Court litigation as a form of recourse for inmates and emphasised the State’s responsibility to prohibit the cruel, inhuman and degrading punishment of inmates. The dissertation has observed that over a period of 20 years of democracy, South Africa’s correctional centre conditions have severely impacted on inmates’ rights directly and indirectly. It concludes that firstly, the primary problem of overcrowding is a global phenomenon and that there is no single solution to fully eradicate its spiralling consequences. Overcrowding infringes on inmates’ foundational rights - rights to accommodation, fair trial, food and privacy. Secondly, the impact of gangsterism and sexual violence in South African correctional centres has severely infringed on inmates’ rights and case law evidences that this correctional centre condition has been 6 ruled as cruel, inhuman and degrading punishment by the United Nations Human Rights Committee. This study observes that the incidence of rape in correctional centres is a common practice and there is a greater risk of transmission of communicable diseases. In the treatment of these communicable diseases, an inmate is dependent on State healthcare facilities. Thirdly, the dissertation concludes that there have been specific instances where there was limited or no access to healthcare facilities which infringed on an inmates’ right to healthcare and life. In this regard, the Constitutional Court has held the State accountable for the infringement of an inmate’s right to access healthcare facilities. Therefore, this dissertation clearly illustrates that South Africa does not comply with its international, regional and domestic obligations. Practical recommendations for reform of South Africa’s correctional centre conditions are then offered so as to prevent the infringement of inmates’ human rights.
A dissertation submitted in fulfilment of the requirements for the degree: Masters of Laws LLM by Dissertation (Research) LAWS8002 Faculty of Commerce, Law and Management - School of Law University of Witwatersrand, 2017
Keywords: Prisoners--Civil rights--South Africa; Prisoners--Legal status, Laws, etc.--South Africa; Criminal justice, Administration of--South Africa